From Capra to Cronenberg (Journal of Parents and Teachers, 2014)
Christmas in the cinema has been and it is the most important topic. The main argument of this article is how it understands this relationship. It makes a review of different Christmas films and their values that they transmit to children and the rest of audience.
Keywords: Christmas; films; values; education; activities.